Analysis of Difficulty Learning Mathematics on Algebra Material Based on Gender - Rahayu, Suci; Cahyani , Resti Endah; Herlina , Yolanda; Kumar, Komil (International Journal of Applied Learning and Research in Algebra, 2024)
This research uses a qualitative descriptive method to describe learning difficulties in class VIII algebra material based on gender. The research subjects comprised 1 class of class VIII junior high school students, male and female. The data collection method used a written test on algebra material, and interviews with students were conducted regarding the written test that had been carried out. The results of this research are that male students have more difficulties than female students. Male students experience difficulties expressing principles and solving problems with solutions that require determining the form of variables but do not have difficulty when expressing the concept of grouping similar terms in algebraic form. Meanwhile, female students do not experience difficulty using the principles of operating algebraic forms and finding the value of a variable but experience difficulties when presenting the concept of grouping similar terms in algebraic form and when solving problems with solutions that require determining the variable form because female students feel confused when working on it—the next step is you do not do the problem until it is finished